Dysfunctional Plasminogen in Full Term Newborn - Study of Active Site of Plasmin - Benavent, A; Estellés, A; Aznar, J; Martinez-Sales, V; Gilabert, J; Fornas, E (Thrombosis and Haemostasis, 1984)
The functional activity and active site of plasmin in full-term newborns have been studied and compared to those in adults in order to investigate the nature of the abnormality found in newborn plasminogen descried in a previous paper.The functional activity of newborn plasminogen measured on chromogenic substrate was approximately 18% that of adult plasminogen when streptokinase was used as an activator and 12% when urokinase was used.Proteolysis of newborn plasminogen by urokinase yielding a two-chain plasmin form occurred normally, but the incorporation of diisopropylphosphorofluoridate into the light chain of newborn plasmin was approximately 23% of that observed in the light chain of adult plasmin.These observations suggest that the abnormality of full-term newborn plasminogen is located in the active site of the molecule.
Keywords: Dysfunctional plasminogen; Full-term newborns; Active site of plasmin